Lesson 8: To use the 'Make ten' strategy to subtract a 1-digit number from a teen number (Part 2) - Oak National Academy (Teacher Hub | Oak National Academy)
Lesson: To use the 'Make ten' strategy to subtract a 1-digit number from a teen number (Part 2)
KerkoCite.ItemAlsoKnownAs: 2486141:2B5M6QKS 4752638:Y79H83C2
Keywords: _C:United Kingdom GBR